2023
DOI: 10.1111/pce.14566
|View full text |Cite
|
Sign up to set email alerts
|

Dark‐induced chloroplast relocation depends on actin filaments in the liverwort Apopellia endiviifolia along with the light‐ and cold‐induced relocations

Abstract: Chloroplasts move to the periclinal walls of cells under weak light to harness light energy for photosynthesis and to anticlinal walls to avoid strong light. These responses involve the cytoskeleton components microtubules and/or actin filaments. In the dark, chloroplasts move to the anticlinal cell walls bordering neighbouring cells (dark‐positioning response), but this response in various plants normally requires a prolonged dark incubation period, which has hampered analysis. However, we recently demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Comparison of the photo-thermochemical data for Aephot and Mpphot revealed that Aephot was less sensitive to variations in light and temperature and showed weaker photoproduct formation for the LOV domain than Mpphot (Figure 1). However, previous studies have reported no notable differences in chloroplast movement responsiveness to light and temperature between A. endiviifolia and M. polymorpha, 18,19,30,31 which raises the following question: How does A. endiviifolia regulate its chloroplast movements under fluctuating light and temperature conditions in nature? We speculate that A. endiviifolia performs a higher activity in Aephot-mediated signaling (e.g., higher Aephot accumulation and kinase activity, and downstream factor functions) for chloroplast movements or it only survives in its kind of habitat only (e.g., shady area with little light fluctuation).…”
Section: Discussionmentioning
confidence: 97%
“…Comparison of the photo-thermochemical data for Aephot and Mpphot revealed that Aephot was less sensitive to variations in light and temperature and showed weaker photoproduct formation for the LOV domain than Mpphot (Figure 1). However, previous studies have reported no notable differences in chloroplast movement responsiveness to light and temperature between A. endiviifolia and M. polymorpha, 18,19,30,31 which raises the following question: How does A. endiviifolia regulate its chloroplast movements under fluctuating light and temperature conditions in nature? We speculate that A. endiviifolia performs a higher activity in Aephot-mediated signaling (e.g., higher Aephot accumulation and kinase activity, and downstream factor functions) for chloroplast movements or it only survives in its kind of habitat only (e.g., shady area with little light fluctuation).…”
Section: Discussionmentioning
confidence: 97%